IMMUNOHISTOCHEMICALLY EVALUATION OF CD20 EXPRESSION IN PATIENTS WITH MULTIPLE MYELOMA - Irfan Yavasoglu; Gokhan Sargin; Gurhan Kadikoylu; Firuzan Kacar Doger; Zahit Bolaman (Mediterranean Journal of Hematology and Infectious Diseases)
Objective: CD20 expression was reported in different rates in patients with multiple myeloma. The importance of this B-cell antigen is still unknown for plasma cells. We aimed to investigate CD20 expression of myeloma cells in bone marrow, also relationship between stage of disease, isotype and clinical features.